The Role of The Website-Based Public Service Information System of The Istiqlal Mosque Management Agency - Hendra Sofyansyah; Erman Anom (Lembaga Komunitas Informasi Teknologi Aceh (KITA), 2023)
This study aims to determine the role of the website-based public service information system www.istiqlal.or.id in terms of visitation to the Istiqlal Mosque, both for service users and for implementers. The Istiqlal Mosque Management Board's impenetrable public relations division has established a new arrangement in the utilization of information technology in the current media era, where public service governance that is eminent in non-worship services is the visitation of a domestic and foreign visitor. The Istiqlal Mosque with its uniqueness, as a state mosque, is also predicated as a cultural heritage building trying to be a trendsetter in the management and service of modern houses of worship, apart from having a central function as a place of worship, it must be able to communicate, be resilient, adaptable and dynamic with an innovative spirit of being an empowered Ummah in Islamic moderation with an Indonesian and global view. The method used is a qualitative research method with a case study approach, the data generated from the collection is based on the facts that appear as they are, which describes the current state of the research object, data collection techniques through observation and interviews, to analyze the data the researchers conducted a depth interview to the sources of service implementers and service users of tourist visitor at the Istiqlal Mosque. The results of this study are that the website-based Public Service Information System specially website-based visitation services at the Istiqlal Mosque can be a role model for mosque information systems, and it is necessary to be properly socialized to the public, to gain wider benefits, and improvements need to be made, gradual and continuously.